Study Motivation in Physical Education for Students With Mild Intellectual Disabilities - Lufthansa, Luthfie; Sumaryanti, Sumaryanti; Ambardini, Rachmah Laksmi; Mustafa, Pinton Setya; Mahardika, Wisnu (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2024)
Physical education learning for students with disabilities must be packaged as well as possible and as interesting as possible. Fostering motivation for students with disabilities in learning physical education is not easy. The purpose of this study was to determine the extent of motivation to learn physical education for mildly disabled students. In this study using quantitative survey method. While the research population was as many as three special school and the research sample was 5th grade students as many as 27 students intelectual disabilities consisting of three spesial school, and this research design used cross sectional. The instrument used a questionnaire of motivation for learning special PE for children with disabilities, where the filling of the motivation questionnaire was carried out by the teacher who taught physical education in the three spesial scholls. While data analysis uses quantitative descriptive analysis. The results of the study are in the excellent classification with an average value of 11% as many as 3 students, the good classification gets an average value of 13% as many as 4 students, the moderate classification gets an average value of 41% as many as 11 students, the classification is less getting an average value of 20% as many as 5 students and the classification is very poor getting an average value of 15% as many as 4 students. From these results, it can be concluded that the level of motivation to learn physical education for students with disabilities is included in the moderate classification.